Autoestima en los adolescentes - Chuquitarco Andrade, Jeniffer Gabriela (2016)
This project aims to know the level of self-esteem in teenegers from 12 to 13 years which is based on a set of skills that make up the self-esteem of each human being because nowadays , they are losing little confidence in them, however, one way or another there are treatments that can strengthen and be used as an aid for individuals with this type of problem. The main teenager in self-esteem is the lack of character of them selves by the fact that the person has not been able to face problems of its surroundings and that will have to learn to be responsible and to confront them with a due solution to be able Integrate into society and contribute frequently. To make known this type of project, the researchers will use a scientific method with the aim of obtaining a greater degree of knowledge on the subject that provide forms of self-help and thus support the investigation deeply entailing signs of alertness and what is the reason why they have a self-esteem So low or taking them to levels and extremes of attack agains their lives, In addition, it was evident the field study since the research was carried out carried or relevant to the porpuse of the proposed….